EFEKTIFITAS PELAKSANAAN PERATURAN DAERAH TENTANG RETRIBUSI / IURAN PASAR DAERAH DI KOTA SURABAYA - Soedjono Soedjono; Nur Handayani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
The purposes of this research is to find out how effective policy of District Regulation about fee / contribution of District Market now prevail in Market Unit that is managed by PD Pasar Surya. Type of this research is policy research and social implementation study cases characteristic. Primary data is gained by closed and opened questionnaire from merchant and employee, also interview with PD Pasar Surya Management. Secondary data is gained from economy sector and PD Pasar Surya.First finding shows that District Regulation Policy about contribution/ Pasar Daerah fee have been implemented by PD Pasar Surya have predicate very effectively successfull. Second finding of PD Pasar Surya expect there are supra-means such as District Regulation Policy or other policy forms that is more moderate as a basic to improve corporation works. Third finding shows there are 4 (four) District Regulation that nomenclature District Degree II City Government Surabaya based on UU RI Number 5 Year 1974, and 1 (one) DPRD Decision Surabaya City Number 42 Year 2000 still based on Law RI Number 22 Year 1999 that in not valid. It is expected the result of this research could give usefully recommendation such as action plan as a solution toward there are policy matter (policy problem) that is felt by PD Pasar Surya Management especially due to effectivity of contribution District Regulation/ Pasar Daerah fee, that is needed for improvement of PD Pasar Surya strategy management, in order to improve its resource.